2007
DOI: 10.24084/repqj05.350
|View full text |Cite
|
Sign up to set email alerts
|

3-phase 4-wire shunt active power filter with renewable energy interface

Abstract: This paper presents a three-phase four-wire Shunt Active Filter that compensates power quality problems and can also interface renewable energy sources with the electric grid. The inverter stage of the active filter is based in a two-level four-leg inverter and its control is based in the Theory of Instantaneous Reactive Power (p-q Theory). The filter is capable of compensating power factor, unbalance, and current harmonics. Additionally it can also make the interface between renewable energy sources and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 3 publications
(4 reference statements)
0
23
0
Order By: Relevance
“…To verify the proposed control technique to achieve multiobjectives for grid interfaced DG systems [8], [9] connected to a 3-phase 4-wire network, an extensive simulation study is carried out using MATLAB/Simulink as shown in Fig.4.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…To verify the proposed control technique to achieve multiobjectives for grid interfaced DG systems [8], [9] connected to a 3-phase 4-wire network, an extensive simulation study is carried out using MATLAB/Simulink as shown in Fig.4.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…A similar approach in which a shunt active filter acts as active conductance to damp out the harmonics in distribution network is proposed in [4]. In [5], a control strategy for renewable interfacing inverter based on -theory is proposed. In this strategy both load and inverter current sensing is required to compensate the load current harmonics.…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach in which a shunt active filter acts as an active conductance to damp out the harmonics in distribution network is proposed in [9]. In [10], a control strategy for renewable interfacing inverter based on p-q theory is proposed. A similar decoupled current control technique using PI regulator in d-q reference frame is presented in [11].…”
mentioning
confidence: 99%